2014
DOI: 10.2478/v10129-011-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seed Health of Perennial Ryegrass (Lolium Perenne L.) on Germination Capacity

Abstract: The analysis of seed health and germination capacity of 7 varieties of Lolium perenne, originated from two breeding station and two seed company localized in different places of Poland, harvested in 2006, 2007 and 2008 were performed. Results of mentioned analysis indicated that seeds were contaminated by numerous species of fungi. The most numerous group of fungi were saprophytes or weak parasites such as: Alternaria alternata, Epicoccum nigrum, Septonema chaetospira and Penicillium spp. Pathogenic species we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A model of seed shattering in monocot or fruit dehiscence in dicot is presented in Figure 1. In monocots, seed shattering is triggered by the formation of an abscission layer at the attachment point between the lemma and pedicel by cell wall thickening and lignification (Harlan and DeWet, 1965;Elgersma et al, 1988;Fuller and Allaby, 2009). Swelling and dissolving of the middle lamella between adjacent cell walls in the abscission layer allows for grain release (Htun et al, 2014).…”
Section: Physiological Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…A model of seed shattering in monocot or fruit dehiscence in dicot is presented in Figure 1. In monocots, seed shattering is triggered by the formation of an abscission layer at the attachment point between the lemma and pedicel by cell wall thickening and lignification (Harlan and DeWet, 1965;Elgersma et al, 1988;Fuller and Allaby, 2009). Swelling and dissolving of the middle lamella between adjacent cell walls in the abscission layer allows for grain release (Htun et al, 2014).…”
Section: Physiological Controlmentioning
confidence: 99%
“…Examination of the spikelet bases between domesticated rice and the wild shattering types revealed that domesticated spikelet bases are characterized by a dimpled appearance and possess less symmetrical scars, whereas the wild types had a smooth scar with a straight profile at the spikelet bases (Li et al, 2006;Fuller et al, 2009). In Lolium spp., the abscission layer is present at the attachment point of lemma and palea to the rachilla (Elgersma et al, 1988). The abscission layer is easily identifiable as the cells present in it are smaller than the parenchymatous cells in the rachilla.…”
Section: Physiological Controlmentioning
confidence: 99%
See 2 more Smart Citations